Perbandingan Transportasi Umum Berbasis Rel di Malaysia dan Indonesia - Novita Fitri Nur Faizah; Roselina Rahmawati; Dimas Ariya Pamungkas; Farhan Raihan Sungkar; Mayvrick Giri Seilendra; Muhammad Daffa Seno Raharjo; Aina Diva Az-Zahra; Cintara Viera Az-Zahra; Dinar Wirayuda (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
This paper compares rail-based public transportation infrastructure (MRT, LRT, KRL) in Malaysia and Indonesia, especially Jakarta and Kuala Lumpur. The primary concern is on MRT, LRT, and KRL as critical elements in the analysis. This research intends to identify the existing transportation conditions in the two countries and analyze the differences and similarities to improve Indonesia's transportation system, especially in Jakarta. Although there are similarities in efforts to provide more efficient, faster, and more comfortable transportation alternatives for the residents of Jakarta and Kuala Lumpur, significant differences can be seen in the development and quality of the transportation system. The transportation system in Malaysia has proven to be more mature and integrated, while Jakarta is still in the development stage. Therefore, Jakarta can take inspiration from Malaysia by focusing improvements on aspects of integration, reliability, implementation of support policies, education campaigns, and expansion of station infrastructure. This research provides a comprehensive picture of the condition of public transportation in both countries and presents recommendations for improving Indonesia's transportation system.